How regional trade agreements deal with disputes concerning their TBT provisions? - Ana Cristina Molina; Vira Khoroshavina (World Trade Organization (WTO), 2018)
Our analysis covers 260 RTAs, of which 200 include at least one provision on TBT. We find that in general disputes on TBT provisions arising under RTAs are not treated differently from other type of RTA disputes. Fifteen per cent of RTAs with TBT provisions include provisions that apply exclusively to the resolution of TBT disputes and do so in general to favour the WTO dispute settlement mechanism over that of the RTA; only in one RTA - NAFTA - do the parties provide under some conditions for the exclusive use of the RTA DSM for certain types of TBT disputes. In the remaining RTAs, the parties do not provide for a specific way of dealing with TBT disputes and apply instead the general dispute settlement (DS) provisions under the RTA. Under the general DS provisions, the parties do not give exclusivity to one forum, with one exception EU-Chile RTA, but allow instead for the selection of the forum in case of jurisdictional overlapping and in accordance with certain rules. RTAs with such a forum-choice clause account for 55% of the RTAs with TBT provisions, while 24% do not provide for any guidelines in the case of jurisdictional overlapping, which can be problematic, and 5% do not have their own dispute settlement mechanism (DSM), so that in the event of a dispute over the same (or similar) obligation under the RTA and the WTO, the WTO DSM would be the only possible forum.
Keywords: F13; F15; 330; dispute settlement; regional trade agreements; non-tariff barriers; TBT